Predictors of preventive behavior in healthy women attending a breast clinic - Βλαβιανού, Μ.; Αναγνωστόπουλος, Φ.; Καρυδά, Ε.; Καλαντζή-Αζίζι, Α. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF